197k views
1 vote
Simplify the expression.

Simplify the expression.-example-1
User LBridge
by
5.4k points

1 Answer

3 votes

Answer:


19 - (6)/(5)j

written out on a computer keyboard, you would type: 19 - (6/5)j

Explanation:

The terms that dont have a 'j' attached to them all group up and combine to this: 18 + (-5) + 6 = 18-5+6 = 13+6 = 19

The rest of the terms have a 'j', and they combine to:
-(2)/(5)j - (4)/(5)j = \left(-(2)/(5) - (4)/(5)\right)j = (-2-4)/(5)j = -(6)/(5)j

After combining both sets of like terms, we have 19 as the first result and
-(6)/(5)j as the second result. They are then added to get
19 + \left(-(6)/(5)j\right) = 19 - (6)/(5)j

We cant simplify any further because there are no like terms left.

User Jimtut
by
5.1k points